Application of a quantum cascade laser aperture scanning near-field optical microscope to the study of a cancer cell. Issue 24 (7th September 2018) - Smith, Caroline I.; Siggel-King, Michele R. F.; Ingham, James; Harrison, Paul; Martin, David S.; Varro, Andrea; Pritchard, D. Mark; Surman, Mark; Barrett, Steve; Weightman, Peter
Abstract : First IR-SNOM images over the Amide I band taken in the centre of an oesophageal cancer cell. Abstract : This work reports the first images obtained by combining an infrared aperture scanning near-field optical microscope (SNOM) with a quantum cascade laser (QCL). The future potential of this set-up is demonstrated by a preliminary study on an OE33 human oesophageal adenocarcinoma cell in which the cell is imaged at 1751 cm −1, 1651 cm −1, 1539 cm −1 and 1242 cm −1 . In addition to the 1651 cm −1 image, three other images were acquired within the Amide I band (1689 cm −1, 1675 cm −1 and 1626 cm −1 ) chosen to correspond to secondary structures of proteins. The four images obtained within the Amide I band show distinct differences demonstrating the potential of this approach to reveal subtle changes in the chemical composition of a cell.